Facile synthesis of ZnO/Zn2TiO4 core/shell nanowires for photocatalytic oxidation of acetone - Wan, L.; Li, Xin Yong; Qu, Z.; Shi, Y.; Li, H.; Zhao, Q.; Chen, G. (Elsevier BV, 2010)
ZnO/Zn2TiO4 core/shell nanowires were synthesized for the first time based on a solid-solid reaction of ZnO nanowires with a conformal shell of TiO2, which was deposited by a sol-gel method. The as-prepared samples were characterized by X-ray diffraction (XRD) analysis, transmission electron microscope (TEM) and environmental scanning electron microscope (ESEM). The surface photovoltage (SPV) spectra indicated that the as-synthesized ZnO/Zn2TiO4 core/shell nanowires exhibited more excellent photovoltaic activity than single ZnO nanowires. The enhanced photocatalytic activity of the ZnO/Zn2TiO4 core/shell nanowires was demonstrated by the degradation of acetone under UV light irradiation. As monitored by the in situ FTIR, a sequence of chemical steps could be extracted during the photocatalytic oxidation of gaseous acetone, which was firstly degraded into formate, and subsequently converted into CO and CO2. CO2 was partially converted to carbonate further. © 2010 Elsevier B.V.